2019
DOI: 10.3390/su11061559
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Wetland Plant Communities and Environmental Factors in the Tumen River Basin in Northeast China

Abstract: Understanding what controls wetland vegetation community composition is vital to conservation and biodiversity management. This study investigates the factors that affect wetland plant communities and distribution in the Tumen River Basin, Northeast China, an internationally important wetland for biodiversity conservation. We recorded floristic composition of herbaceous plants, soil properties, and microclimatic variables in 177, 1 × 1 m 2 quadrats at 45 sites, located upstream (26), midstream (12), and downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Spatial soil nutrient gradients have been widely reported to shape the distribution and composition of wetland vegetation communities (Graham & Mendelssohn, 2016;Ma et al, 2021;Zheng et al, 2019), and unsurprisingly, we found that soil organic carbon, nitrogen, and pH, three variables closely related to soil nutrient availability to wetland plants, were the most important soil factors to species suitability in wetlands. Specifically, nitrogen is the predominant limiting nutrient that regulates plant growth and productivity of wetland ecosystems (Bai et al, 2012;Mitsch & Gosselink, 2015;Olde Venterink et al, 2001), and pH not only impacts directly on plant physiological processes, but also influences the availability and toxicity of certain critical elements for wetland plants, such as phosphorus, potassium, iron, and sulfur (Cheng et al, 2020;Mitsch & Gosselink, 2015;Tercero et al, 2015).…”
Section: The Influence Of Abiotic Factors and Anthropogenic Disturban...mentioning
confidence: 74%
See 1 more Smart Citation
“…Spatial soil nutrient gradients have been widely reported to shape the distribution and composition of wetland vegetation communities (Graham & Mendelssohn, 2016;Ma et al, 2021;Zheng et al, 2019), and unsurprisingly, we found that soil organic carbon, nitrogen, and pH, three variables closely related to soil nutrient availability to wetland plants, were the most important soil factors to species suitability in wetlands. Specifically, nitrogen is the predominant limiting nutrient that regulates plant growth and productivity of wetland ecosystems (Bai et al, 2012;Mitsch & Gosselink, 2015;Olde Venterink et al, 2001), and pH not only impacts directly on plant physiological processes, but also influences the availability and toxicity of certain critical elements for wetland plants, such as phosphorus, potassium, iron, and sulfur (Cheng et al, 2020;Mitsch & Gosselink, 2015;Tercero et al, 2015).…”
Section: The Influence Of Abiotic Factors and Anthropogenic Disturban...mentioning
confidence: 74%
“…Simultaneously, wetland vegetation is particularly susceptible to changes of key environmental elements in wetlands (e.g., water table depth, nutrient conditions) that could be directly and indirectly induced by human activities and climate change (Ficken et al., 2019; Short et al., 2016). Thus, proper wetland protection requires understanding the relationships between the spatial patterns of wetland plant species and their environment, and how future environmental changes potentially alter species suitability in wetlands (Moor et al., 2015; Short et al., 2016; Zheng et al., 2019). Generally, climatic factors, especially factors controlling water supply and seasonal hydrologic pulsing of wetlands (e.g., precipitation of the growing season, snowfall, isothermality), are recognized to be central in governing wetland species distributions at larger geographical scales (Garris et al., 2015; Xue et al., 2018; Zhong et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers [33][34][35] concluded that the protection efficiency of the WNNR in NEC needs to be improved. According to legislation for WNNR, no agricultural activities are allowed in the national protected areas.…”
Section: Ecological Conservation Levels Characterized By the Legislat...mentioning
confidence: 99%
“…Positive relationships between plant diversity and environmental factors are common in various vegetation types (Balvanera & Aguirre, 2006; Beck et al, 2011; Slik et al, 2009; Zheng et al, 2019) and ecological gradients (Maharjan et al, 2021; Song et al, 2021; Tolmos et al, 2022; Venter et al, 2017; Wittmann et al, 2006). The available remote sensing environmental data provide spatially refined information on landscape and vegetation heterogeneity over the Amazon basin that can be readily incorporated into spatial models to study diversity distribution patterns.…”
Section: Introductionmentioning
confidence: 99%